Spatial Information System for Housing Data Collection at The Department Of Public Housing and Settlement Areas - Vatresia, Arie; Utama, Ferzha Putra; Sugianto, Nanang; Turrahma, Ridha Nafila (Jurnal Teknik Informatika (Jutif), 2026)
The Bengkulu City Public Housing and Settlement Agency is a government agency tasked with assisting the mayor in administering government affairs related to public housing, settlement areas, and land matters under regional jurisdiction. In addition, the Department of Public Housing and Settlement Areas also has an obligation to serve the community and always strives to provide the best service information to the community, especially in Bengkulu City. This is particularly true in terms of housing data collection processed by the Department of Public Housing and Settlement Areas in Bengkulu City. The housing data collection system used for office purposes in terms of monthly or annual reports and archives at the Public Housing and Settlement Agency is not yet computerized. However, to date, these main activities are still carried out manually. The storage of this data is also still piled up in cabinets, which requires a long time to create reports and search for the data itself. This need can be facilitated by the existence of computational products and algorithms in the Informatics program that synergize with Geophysics in addressing data collection and landscape analysis issues related to housing and settlements. The implementation of this integrated system improves the management process of plot pattern data, basic infrastructure, uninhabitable house, and developer.  This research showed that the total calculation, the average System Usability Testing score obtained was 62.5, which falls under the good category. This indicates that the developed system meets usability standards and is well accepted by its users.